Maternal Antibiotic Treatment Disrupts the Intestinal Microbiota and Intestinal Development in Neonatal Mice - Chen, Chung-Ming; Chou, Hsiu-Chu; Yang, Yu-Chen S. H. (Frontiers in Microbiology, 2021)
Maternal antibiotic treatment (MAT) during prenatal and intrapartum periods alters the bacterial composition and diversity of the intestinal microbiota of the offspring. The effect of MAT during pregnancy on the intestinal microbiota and its relationship with intestinal development remain unknown. This study investigated the effects of MAT during pregnancy on intestinal microbiota, injury and inflammation, vascularization, cellular proliferation, and the intestinal barrier in neonatal mice. At timed intervals, we fed pregnant C57BL/6N mice sterile drinking water containing antibiotics (ampicillin, gentamicin, and vancomycin; all 1 mg/ml) from gestational day 15 to delivery. The control dams were fed sterile drinking water. Antibiotic administration was halted immediately after birth. On postnatal day 7, the intestinal microbiota was sampled from the lower gastrointestinal tract and the ileum was harvested for histology, Western blot, and cytokines analyses. MAT significantly reduced the relative abundance of Bacteroidetes and Firmicutes and significantly increased the relative abundance of Proteobacteria in the intestine compared with their abundances in the control group. MAT also significantly increased intestinal injury score and cytokine levels, reduced the number of intestinal goblet cells and proliferating cell nuclear antigen-positive cells, and reduced the expressions of vascular endothelial growth factor and tight junction proteins. Therefore, we proposed that maternal antibiotic exposure during pregnancy disrupts the intestinal microbiota and intestinal development in neonatal mice.